PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP KUALITAS TIDUR LANSIA YANG MENGALAMI GANGGUAN TIDUR DI KLINIK ALAM SEHAT KABIL BATAM - Era Zana Nisa; Corry Nova Adelina Manurung (Poltekkes Kemenkes Medan, 2025)
This study aims to determine the effect of Progressive Muscle Relaxation Therapy on the sleep quality of elderly people experiencing sleep disorders at the Alam Sehat Kabil Clinic in Batam. The background of this study is based on the high number of elderly people who experience sleep problems, such as difficulty falling asleep and sometimes waking up during the night and being unable to fall back asleep. This study used a quasi-experimental approach, aiming to reveal the effect of adaptive manipulation on participants. The approach used in this study was a one-group pre- and post-test design. The results concluded that Progressive Muscle Relaxation Therapy has an effect on the sleep quality of elderly people experiencing sleep disorders at the Alam Sehat Kabil Clinic in Batam, with a p-value of 0.000 < 0.05.